Implementasi Religius Culture dalam Upaya Membentuk Perilaku Disiplin Siswa SD Al-Ma’soem Bandung - Ahsani, Eva Luthfi Fakhru; Hilmiah, Akif; Lusiana, Yusria; Wijayanti, Dhivani Artha (Lembaga Yasin AlSys, 2022)
This study aims to determine the religious character education program developed at SD Al-Ma'soem Bandung, to determine the character education program developed at SD Al-Ma'some Bandung, to describe the implementation of the religious character and discipline of students at SD Ma'soem Bandung. The research method used is descriptive method with a qualitative approach and literature study. The population of this study were students and educators of SD Al-Ma'soem. The results showed that the form of implementation of the religious character and discipline of students at SD Al-Ma'soem Bandung by providing internalization of religious character education and discipline, students to follow all programs that have been made, especially religious and disciplinary programs that provide good examples for students educate.